PARTISIPASI ANGGOTA BADAN TADZKIR DALAM MENJALANKAN TUGAS DAN FUNGSI KAJIAN SOSIOLOGI ORGANISASI (STUDI KASUS DI FISIP UNSRAT) - Dukomalamo, Gafur; Mokalu, Benedicta J.; Tumengkol, Selvie M. (HOLISTIK, Journal Of Social and Culture, 2020)
Human beings are living things that have desires and various needs. It is this condition that causes humans to be often referred to as the wanting creature. To fulfill all desires, needs until the point of satisfaction is reached, in addition to making several efforts / actions, one also needs a variety of tools. Human beings begin to realize, only through cooperation within the organization, will he obtain effective and efficient work, and therefore man desperately needs the organization. In organizing each individual can interact with all related structures either directly or indirectly to the organization they choose.Every organization must have a goal, whether a single goal or multiple goals. This principle seems to have become an axiom, that organization is merely a tool for achieving a goal, not a goal itself. The consequence of this is that each part of the organization must contribute or contribute to the achievement of the overall objectives of those parts and each section must have its own clear objectives in order to support the achievement of the general objectives of the organization.A student organization that forms a shared life in which its members are bound by pure and natural and eternal inner relationships. The basis of the relationship is the sense of love and inner unity of fellow Muslims that has indeed been bonded. Badan Tadzkir FISIP UNSRAT itself belongs to a group of students in which the group itself is born from a binding equation among the members of the group. The direct participation of members in Badan Tadzkir is seen in two forms, namely planting the values of the brotherhood of fellow Muslims through a forum of friendship. As well as being willing to help the difficulties of every member on campus.Keywords: organization, student, campus